A low power, temperature-invariant frequency source - Tan, Wei Lin (2017)
Clock signals are a necessity in most digital electronic systems to synchronise various parts of the integrated circuit. As a time reference, the clock signal’s frequency should be accurate and constant. Temperature invariance and power consumption are two key specifications for an on-chip oscillator. Using 65nm CMOS process, this paper proposes a low-power on-chip temperature-invariant clock of 0.24% frequency variation across -40°C to 125°C about 1 MHz, consuming 367uW at 3.3V supply voltage. Across three process corners, its largest frequency variance is 0.46% and its maximum power consumption is 471uW. The circuit is also supply-independent and resistor process-independent. The proposed design uses switched capacitors to track the output frequency of the oscillator. When the loop is in equilibrium, current through the switched capacitor will be equal to the reference current and the frequency of the oscillator reaches steady state. By designing the reference current to be constant with temperature, the oscillation frequency can be made less sensitive to temperature changes. If the frequency drifts, current through the switched capacitor changes, resulting in a net current flowing in or out of the integrator, whose output voltage controls the frequency of the oscillator. Through the negative feedback loop, the oscillator will be adjusted back to its equilibrium frequency.